Modern techniques of teaching and learning in medical education: a descriptive literature review - Krishna Teja Challa; A Mosavi Sayed; Yogesh Acharya (2021)
MedEdPublish (ISSN 2312–7996) is a highly visible, open access, specialist practitioner e-journal that enables academics, teachers, clinicians, researchers and students to publish their experiences, views and research findings relating to teaching, learning and assessment in medical and health professions education. An innovative and key feature of MedEdPublish is that the peer review process begins following publication.